EFFECT OF SITE AND COMPETITION ON DIAMETER GROWTH OF Araucaria angustifolia - Dobner Jr., Mário; Paixão, Crysttian Arantes; Costa, Emanuel Arnoni; Finger, Cesar Augusto Guimarães (Floresta, 2019)
Although the historical interest in using the wood of Araucaria angustifolia, it is still little known concerning the factors that affect the growth. A broader understanding in this context might contribute to the development of appropriate management systems, thus increasing the productivity of plantations and, consequently, the interest in commercially using this species. The present study was based on monospecific populations established in different site conditions (Site Indices between 18-24) where individuals (n=654) were submitted to different competition levels. With the aid of multiple regression techniques, the factors that significantly affected the accumulated growth in diameter of the trees after 20 years of intervention were determined. For the set formed by all trees, 77% of the growth variation can be explained by three factors: site, the proportion of tree diameter at breast height (dbh) of the object tree for analysis in relation to the average dbh of the population before performing the clearings (Cdbh_before) and dominance status in relation to the neighboring trees (Call). The significance of the competition level before the clearing shows that late clearings have limited effects on tree growth. It is concluded that individuals are benefited for having a dominant position in relation to the neighboring trees, reaching diameters 50% larger at the end of the production cycle. Clearings that favour selected trees by removing direct competitors seem to be an interesting management strategy for the species. Keywords: Paraná-pine; Forest Management; Silviculture; Timber Production.